Manajemen Pendidikan Islam: Kolaborasi Antara Nilai Spiritual dan Pengelolaan Pendidikan - Yovica, Alia; Oktavia, Lidya Fransiska; Refnawati, Refnawati; Zahara, Sri; Hidayat, Rahmad (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Islamic education management is a discipline that not only focuses on the technical aspects of the management of educational institutions, but also incorporates Islamic spiritual and moral values at every stage of education. This article aims to find out the collaboration between spiritual values and educational management in Islamic education management. This study uses a literature study method with a systematic approach to review previous studies related to research topics. The data sources used come from scientific journals indexed in databases such as Google Scholar. The selected articles meet the inclusion criteria, namely published in the last five years. The analysis is carried out by identifying, comparing, and grouping the results of existing research, to formulate a comprehensive conclusion. The results of the analysis show that the fundamentals of Islamic education management include principles based on the teachings of the Qur'an, Hadith, and a strong Islamic scientific tradition. Islamic education has the main goal of forming people who are faithful, knowledgeable, and have noble character, where the entire educational process is directed to achieve harmony between science and Islamic values. In its implementation, Islamic education emphasizes the importance of faith (Tauhid), deliberation (Shura), justice (Adil), and goodness (Ihsan), which must be applied in school management, teaching processes, and relationships between individuals in the educational environment